Dysbiosis of oral buccal mucosa microbiota in patients with oral lichen planus. (31st March 2017) - He, Y; Gong, D; Shi, C; Shao, F; Shi, J; Fei, J
Abstract : Objective: The bacterial community structure of buccal mucosa in patients with oral lichen planus was evaluated and compared with healthy control. Subjects and Methods: Buccal scraping samples have been taken on 43 oral lichen planus patients (21 erosive and 22 non‐erosive) and 21 mucosal healthy volunteers. The V3 hypervariable 16S rDNA region was amplified and sequenced by high‐throughput 454 pyrosequencing. Results: 94.26% of the total buccal bacteria were classified into 15 abundant genera. Eight of these abundant genera could be detected in all cases, namely Streptococcus, Prevotella, Haemophilu, Neisseria, Fusobacterium, Leptotrichia, Veillonella and Actinomyces . Four abundant bacteria showed significantly different prevalence at the genus level: Streptococcus was more abundant ( P  < 0.01) in healthy control group, while Fusobacterium ( P  < 0.01), Leptotrichia ( P  < 0.001) and Lautropia ( P  < 0.001) showed higher abundance in OLP group. Few differences can be found between erosive and non‐erosive OLP. In general, 19 'core' OTUs at three levels were defined to be OLP specific, comparing with healthy control group. Conclusions: These results suggest that OLP is associated with dysbiosis of the oral microbiome. Further studies should be taken to elucidate the inner relationship between these observed changes and OLP development.